Efeitos hemodinâmicos da infusão contínua de butorfanol em cães anestesiados com propofol - Barbosa, Vivian Fernanda; Nunes, Newton [UNESP]; Santos, Paulo Sérgio Patto [UNESP]; Moro, Juliana Vitti [UNESP]; Thiesen, Roberto; Belmonte, Emílio Almeida (FapUNIFESP (SciELO), 2015)
The aim of this study was to evaluate the hemodynamic effects of the total intravenous anesthesia with propofol and butorphanol in dogs. For that purpose, twenty adult healthy crossbred dogs were used. The animals were equally allocated into two groups (PG and BG) and induced to the anesthesia with intravenous propofol (10 mg/kg). After orotracheal intubation, controlled ventilation was instituted with 60% oxygen and flow of 30 mL/kg/min in a closed system, with controlled volume. The anesthetic maintenance was accomplished with propofol (0.6 mg/kg/min). The butorphanol group (BG) received, butorphanol 0.1 mg/kg IV, followed by continuous infusion (40 μg/kg/h). The placebo group (PG) received only NaCl 0.9% in bolus, followed by venous infusion, in identical volume of the BG. Baseline hemodynamic measurements were performed before opioid or saline administration (M0) and immediately after, every 15 minutes (M15 to M75). Administration of butorphanol resulted in decrease of total peripheric resistance (TPR), arterial pressures (SAP, DAP, MAP) and cardiac output (CO), without clinical relevance. The results allow us to conclude that association provides safe anesthesia for patients with ventilatory support.
Hemodinamic effects of continuous rate infusion of butorphanol in propofol-anesthetized dogs
Keywords: Monitoring; Opioid; Total intravenous anesthesia